The Effect of Education, Recruitment and Work Facilities on Employee Performance and Job Satisfaction as Intervening Variables at PT GAG NIKEL - Sunatar, Bambang (Universitas Mercu Buana, 2023)
Objectives: The success of the company's institutions and organizations is inseparable from the support of its employees in seeking to improve their performance so that the ability and job satisfaction of its employees is very important to be given more attention to achieve the desired success or goals of the company. Therefore a company or organization must really pay attention to its employees by means of recruitment processes, education, and also work facilities that must support them. This is done in order to improve employee performance and job satisfaction.Methodology: The method used in this study is to use a quantitative descriptive method. This study uses the PLS SEM model analysis for data processing. The sample used uses a saturated sample, namely all employees of PT Gag Nikel, totaling 68 people.Conclusion: Recruitment and work facilities have a significant effect on job satisfaction. Recruitment and work facilities also have a significant influence on employee performance. While education has no significant effect on job satisfaction and education also has no effect on performance. Job satisfaction also has no significant effect on employee performance.